Analysis of Company Value With Liquidity as a Moderating Variable in Food and Beverage Sub-Sector Companies on the Indonesia Stock Exchange - Katherine Situmorang; Yuniningsih Yuniningsih (Indonesian Interdisciplinary Journal of Sharia Economics (IIJSE), 2025)
This study aims to analyze the influence of investment decisions, dividend policy, and leverage on firm value, with liquidity as a moderating variable in food and beverage sub-sector companies listed on the Indonesia Stock Exchange for the 2020-2023 period. This study uses a quantitative method with Moderated Regression Analysis. The study population comprised food and beverage sub-sector companies listed on the Indonesia Stock Exchange for the 2020-2023 period, with a sample of 13 companies using a purposive sampling technique. The results indicate that investment decisions do not contribute to firm value, dividend policy does not contribute to firm value, and leverage contributes to firm value. Liquidity does not moderate the relationship between investment decisions and firm value, but liquidity can moderate the relationship between dividend policy and firm value, and liquidity also moderates the relationship between leverage and firm value. This study recommends companies to manage internal funds efficiently, avoid excessive debt use, and consider the feasibility of investments that can increase firm value.